Turismo de base comunitária como campo de possibilidades para a cooperação transfronteiriça entre Brasil e Bolívia - Amarilio, Francisco Leonor de (2025)
This work was born out of the need to analyze and reflect on community-based tourism and its field of possibilities for cross-border cooperation, taking as a stage of studies the border community of professional artisanal fishermen in the municipality of Corumbá-MS, in Brazil and the community of artisanal fishermen of Puerto Quijarro, in Bolivia. The research initially proved to be bibliographic, with consultations on electronic platforms such as the Capes periodical portal, printed newspapers, magazines and books. However, the research assumed the character of participatory action research because we believe in praxis, which theory should not separate from practice. We went into the field, with interviews, informal conversations and conversation circles, both in Brazil and Bolivia. Notoriously, the work was more important on the Brazilian side, where fishermen are already organized politically and professionally and have been working for generations, which is not the case on the Bolivian side. This is an investigative work, on the possibilities of border cooperation through community-based tourism (TBC), a theme that was born from the problematizations, which made the writing of the work possible: in the case of different nations, will the TBC be presents itself as a field of possibilities for cross-border cooperation? Does the border under study have local potential that could encourage and boost tourism activities through mutual cooperation? The border space being studied refers to the municipality of Corumbá-MS (Brazil) and Puerto Quijarro (Bolivia). A work of this nature presents its justification in the fact that professional artisanal fishermen are going through a process of devaluation of their activities by public authorities and due to the emphasis on tourism activities that are taking place in the region. In this thesis, we intend to show that the tourist territory results from tourist practice and based on this thought, it is clear that tourist practices reveal different territorialities and, succinctly, the territorialities in this work can be understood as the use made of the territory. This thesis is therefore concerned with analyzing whether community-based tourism activities (CBT) can generate development and improvements in the quality of life of professional artisanal fishermen, and whether border cooperation, on the part of managers, planners and social actors who considerin g local interests and potential, they can boost tourism, increase the revenue of border municipalities and assist in the development of the TBC.